2010
DOI: 10.1161/circulationaha.110.958033
|View full text |Cite
|
Sign up to set email alerts
|

Silent Information Regulator 1 Protects the Heart From Ischemia/Reperfusion

Abstract: Background-Silent information regulator 1 (Sirt1), a class III histone deacetylase, retards aging and protects the heart from oxidative stress. We here examined whether Sirt1 is protective against myocardial ischemia/reperfusion (I/R). Methods and Results-Protein and mRNA expression of Sirt1 is significantly reduced by I/R. Cardiac-specific Sirt1 Ϫ/Ϫ mice exhibited a significant increase (44Ϯ5% versus 15Ϯ5%; Pϭ0.01) in the size of myocardial infarction/area at risk. In transgenic mice with cardiac-specific ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
417
4
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(450 citation statements)
references
References 36 publications
25
417
4
4
Order By: Relevance
“…It was shown that Resv protects H9c2 cells from hypoxia-induced apoptosis by signaling via the SIRT1-FOXO1 pathway [15]. Moreover, SIRT1-induced upregulation of antioxidants and downregulation of pro-apoptotic molecules, via FOXO activation and reduction of oxidative stress, protecting transgenic mice from IR-induced cardiac injury [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that Resv protects H9c2 cells from hypoxia-induced apoptosis by signaling via the SIRT1-FOXO1 pathway [15]. Moreover, SIRT1-induced upregulation of antioxidants and downregulation of pro-apoptotic molecules, via FOXO activation and reduction of oxidative stress, protecting transgenic mice from IR-induced cardiac injury [30].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Hsu and colleagues found that SIRT1 upregulates the expression of cardioprotective molecules, such as MnSOD, Trx1, and Bcl-xL, and at the same time downregulates pro-apoptotic molecules, including Bax [30]. SIRT1 is also known to deacetylate FOXO, leading to upregulated expression of genes involved in cell-protective processes [34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IPC increased SIRT1 enzymatic activity and neuroprotection in an in vivo rat model of cardiac arrest [114]. SIRT1 is also activated in the heart following IPC and provides cardioprotection from ischemia and coronary artery occlusion [115][116][117].…”
Section: Sirt1mentioning
confidence: 98%
“…Therefore, it seems that oxidants could affect sirtuins via depletion of NAD þ and oxidative modification of amino acid residues, leading to decreased activity or level of the enzyme [40,44]. On the other hand, it has also been shown that the overexpression of SIRT1 has beneficial effects in resistance to oxidative stress [39,44,45].…”
Section: Redox Balance and Sirtuins: Up-and Downstream Regulatorsmentioning
confidence: 99%